#
Hello,

**I need to factor out **

x^2 - 7x +12 *= 0*

**and this is what I did...**

**I factored out the -7x **

*⇒ x^2 - 4x - 3x +12 = 0*

**Then I grouped them**

⇒ (x^2 - 4x) - (3x +12) = 0

⇒ x (x - 4) - (????) = 0

*That's where I'm lost*

I can't seem to be able to factor out -(3x+12) into having a factor of (x-4)

it always comes out as -3(x+4)

I hope someone can help. :)

2
x^2 - 7x +12

*That's where I'm lost*

I can't seem to be able to factor out -(3x+12) into having a factor of (x-4)

it always comes out as -3(x+4)

I hope someone can help. :)

I can't seem to be able to factor out -(3x+12) into having a factor of (x-4)

it always comes out as -3(x+4)

I hope someone can help. :)

by Tobi

Log in to add a comment